Dosimetric effects of the ipsilateral shoulder position variations in the sitting-positioned boron neutron capture therapy for lower neck tumor. (October 2022) - Kato, Ryohei; Hirose, Katsumi; Kato, Takahiro; Motoyanagi, Tomoaki; Arai, Kazuhiro; Harada, Takaomi; Takeuchi, Akihiko; Yamazaki, Yuhei; Narita, Yuki; Komori, Shinya; Sato, Mariko; Takai, Yoshihiro
Abstract: We aimed to evaluate dosimetric effects of ipsilateral shoulder position variations (ISPVs) in sitting-positioned boron neutron capture therapy (BNCT) for lower neck tumor. The ISPVs were simulated using deformed shoulder images that can simulate arbitrary shape. The dose–volume parameters for the tumor in the rotated shoulder plans considerably varied compared with that for the mucosa. Even in a small number of cases, these differences were clearly observed among patients. The ISPVs in lower neck BNCT have great dosimetric effects. Highlights: Effects of ipsilateral shoulder position variations (ISPVs) were investigated. Differences of the dosimetric effects were clearly observed among patients. The ISPVs in lower neck BNCT have great dosimetric effects.